Analysis of Peat Soil Chemical Properties in Oil Palm Plantation in Simpang Kanan Village, Rokan Hilir Regency - vivi indah sari; Badrul Ainy Dalimunthe; Fitra Syawal Harahap; Hilwa Walida (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
This ecosystem change results in changes in chemical, physical, and biological characteristics and properties. The fertility level of peatlands can be determined through an analysis of the chemical properties of the soil. Therefore, the analysis of the chemical properties of the soil, including the analysis of the main nutrient content, was carried out from November 2021 to January 2022 in Simpang Kanan Village, Simpang Kanan District, Rokan Hilir Regency, Riau Province. Farmers in Simpang Kanan Village use marginal land, that is peat soil to develop oil palm farming. This research was conducted using the free grid method at the semi-detailed survey level. The implementation of taking soil samples from 3 sample points with a distance of 100 meters in the field using a random method scattered at predetermined points. Farmers in Simpang Kanan Village use marginal peat soil to cultivate oil palm plantations. So far, no analysis of the chemical properties of peat soil has been carried out. Application of fertilizers and cultivation is only based on knowledge from the internet or from previous generations. Therefore, it is important to study the analysis of the chemical properties of soil from peatlands used for oil palm plantations. The results of research on the chemical properties of peatlands in Simpang Kanan Village, Simpang Kanan District, Rokan Hilir Regency, Riau Province showed that the peat soil planted with oil palm in Simpang Kanan Village had a pH of around 4.89, C-organic 6.07%, N-Total 1 ,67 mg/L , P-Total 34.08 mg/L , K-Total 11.54 mg/L. Thus, the chemical properties of the soil in oil palm plantations in Simpang Kanan Village, Simpang Kanan District, Rokan Hilir Regency, Riau Province. Still good, to increase fertility for oil palm cultivation, it can be done by increasing the pH in the soil so that it maximizes oil palm development and can be used as a recommendation for oil palm fertilization.